Escenarios de explotación sexual comercial de niños, niñas y adolescentes, modalidad abierta, Medellín, 2012 (2016)
ABSTRACT: Commercial sexual exploitation of children and adolescents (cseca) is a severe violation of the rights of children and adolescents. In Medellin, data on the quantity and locations where this issue takes place is scarce, and it could be useful for implementing strategies for preventing and addressing this issue. Objective: To describe the magnitude of street-based cseca along with the places, days, hours and characteristics of the scenarios in which it takes place in Medellín. Methodology: A descriptive study in which geographical information systems where used to draw thematic maps. The study had three stages: pre-mapping, mapping and validation. In addition, qualitative techniques were used. Results: Of the 634 areas visited, 18.9% had reported cases of cseca. The phenomenon was found to be concentrated in 11 cluster areas exhibiting the following context factors that favor cseca: problems with street lighting, insufficient presence of the State and the local police, drug trafficking, existence of bars, hotels and massage parlors in the area, social permissiveness, easy access to drugs and lodging. Conclusion: georeferencing these areas and identifying the contextual factors behind this situation is very important if this problem, which violates the rights of children and adolescents, is to be controlled and eradicated.